WHAT CAN MODERN FARMERS’ DO? - Muslikhun, Muslikhun; Sitepu, Rismawati Br; Hameed, Amjad (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Farming, a profession that has been present since the dawn of humanity, has thrived due to the vast and fertile land surrounding human settlements. However, in various regions, the younger generation is increasingly abandoning this occupation. Despite this trend, farming remains a crucial means of meeting daily needs in many parts of the world. Unfortunately, the rapid pace of development has resulted in a decline in traditional agricultural land. Consequently, urban farming has emerged as a solution in numerous cities worldwide. This qualitative article aims to emphasize the rise of urban farming as a new cultural phenomenon embraced with great enthusiasm by individuals. Its primary objective is to shed light on the increasing popularity of urban farming and its impact on both individuals and communities. The study's findings demonstrate that promoting urban farming, including hydroponic systems, can address unemployment and boost economic productivity.